Clinical Classification and Collateral Circulation in Chronic Cerebrospinal Venous Insufficiency - Wang, Zhongao; Ding, Jiayue; Bai, Chaobo; Ding, Yuchuan; Ji, Xunming; Meng, Ran (Frontiers in Neurology, 2020)
Background: As an indispensable part of cerebral venous system, the jugular venous system is not fully recognized. This study aimed to analyze the clinical classification and imaging characteristics of internal jugular venous outflow insufficiency (IJVOI) quantitatively. Methods: A total of 128 patients, who were diagnosed as IJVOI by jugular ultrasound and contrast-enhanced magnetic resonance venography (CE-MRV), were enrolled from May 2018 through May 2019. For the patients with possible extraluminal compression, computed tomography venography (CTV) was applied to estimate the degree of internal jugular venous stenosis (IJVS) and rank the vertebral venous collateral circulation. Results: The causes of extraluminal compression induced IJVS included osseous compression (78.95%), carotid artery (24.21%), sternocleidomastoid muscle (5.79%), swollen lymph node (1.05%) and unknown reasons (5.26%). The subtypes of non-compression IJVOI included high jugular bulb (77.27%), fenestration of internal jugular vein (IJV) (7.27%), internal jugular phlebectasia (2.73%), tortuous IJV (0.91%), IJV thrombosis (14.55%) and elongated venous valves with/without erythrocyte aggregation (13.64%). For extraluminal compression induced IJVS, the ratio of severe vertebral venous expansion was higher in the severe IJVS group than that in the mild IJVS group (p < 0.001). The IJVS degree was higher in the severe vertebral venous expansion group than that in the mild vertebral venous expansion group (p < 0.001). Conclusions: A multimodal diagnostic system is necessary to improve the diagnostic accuracy of IJVOI. Vertebral venous system is the major collateral circulation for IJVOI, which may be a promising indicator for evaluating IJVS degree.